The Body Artist by Don DeLillo: A Baudrillardian nalysis (مجلة ديالى للبحوث الانسانية, 2025)
The present research examines the postmodern ideas of Jean Baudrillard and conducts an analysis of the manifestation of the notions of hyperreality and simulation within the context of this particular book. In the realm of hyperreality, an artificially constructed version of reality that has only superficial resemblances to actuality and without any substantive foundation, serves as a replacement for genuine reality. This study examines the occurrence of hyperreality and simulation in the Body Artist, focusing on several key issues. These include the multiplicity and fluidity of identities within both the artistic performance and the main narrative, the deliberate blurring of boundaries between fiction and reality through the use of playful elements within the Body Artist, the emergence of simulacra, the presence of circular recursion, and the captivating influence of media. Hence, the central character, Lauren Hartke, surpasses the boundaries that separate the realms of actuality and imagination via her iterative transformations inside the realm of her artistic expression known as Body Time.